Normal tension glaucoma: from the brain to the eye or the inverse? - Zhang, Hui-Jun; Mi, Xue-Song; So, Kwok-Fai (Neural regeneration research, 2019)
Glaucoma is a chronic, progressive optic neuropathy characterized by the loss of peripheral vision first and then central vision. Clinically, normal tension glaucoma is considered a special subtype of glaucoma, in which the patient's intraocular pressure is within the normal range, but the patient experiences typical glaucomatous changes. However, increasing evidence has challenged the traditional pathophysiological view of normal tension glaucoma, which is based only on intraocular pressure, and breakthroughs in central nervous system imaging may now greatly increase our knowledge about the mechanisms underlying normal tension glaucoma. In this article, we review the latest progress in understanding the pathogenesis of normal tension glaucoma and in developing imaging techniques to detect it, to strengthen the appreciation for the connection between normal tension glaucoma and the brain.